Risk Assessment Decisions in Banking and Finance - Bol, Georg.; Rachev, Svetlozar T.; Würth, Reinhold. (Contributions to Economics, 2009)
New developments in assessing and managing risk are discussed in this volume. Addressing both practitioners in the banking sector and research institutions, the book provides a manifold view on the most-discussed topics in finance. Among the subjects treated are important issues such as: risk measures and allocation of risks, factor modeling, risk premia in the hedge funds industry and credit risk management. The volume provides an overview of recent developments as well as future trends in the area of risk assessment.